2019
DOI: 10.1016/j.heliyon.2019.e02712
|View full text |Cite
|
Sign up to set email alerts
|

Development of ceiling board using breadfruit seed coat and recycled low density polyethylene

Abstract: Conversion of agro wastes into potential raw materials for production has gained a lot of attention in research. This has led to the development of ceiling board using waste breadfruit seed coat and Recycled Low Density Polyethylene, as filler and binder respectively. The filler material (Breadfruit seed coat), was treated with 1 mol/dm3 of NaOH to eliminate the pigment and neutralized using 0.5 mol/dm3 Acetic Acid. After drying, the filler material was ground to a particle size of 600μm. Using Central Composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 5 publications
(7 reference statements)
4
17
0
Order By: Relevance
“…The increase in pressure on the other hand also reduces the moisture content of the material. This findings agree with that of Ezenwa et al. (2019) .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The increase in pressure on the other hand also reduces the moisture content of the material. This findings agree with that of Ezenwa et al. (2019) .…”
Section: Resultssupporting
confidence: 92%
“…This is true because if the press time increases the effect of pressure on the material will cause an increase in the amount of moisture content lost. This negative effect of press time and pressure was also reported by Ezenwa et al. (2019) in their research.…”
Section: Resultssupporting
confidence: 80%
“…Several biomasses have been investigated as fillers in LDPE polymer matrix, these include breadfruit seed coat [13], olive stone [11], snail shell [14] wood fiber [15], palm kernel shell fiber [16], groundnut shell [17]. Recent works also reported other applications of LDPE waste as construction materials in plastic bonded sand block [9], lightweight concrete [18] and hydrophobic surface coating [19].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, improving the thermal environment and efficient green energy production [10]. Also, study by Ezenwa et al [11] showed that optimization of the process parameters like press pressure, press time, and press temperature during ceiling composite production would lead to a ceiling product of adequate physical and thermal characteristics. However, the comparison of the insulation properties with the interfacial heat transfer coefficient remained a major problem to ceiling materialists [12].…”
Section: Introductionmentioning
confidence: 99%